Book Review - Susan J. Behrens (Names)
Names, Naming, and the Law: Onomastics, Identity, Power, and Policy. Edited by I. M. Nick. New York: Routledge. 2023. Pp. 226 (Hardback). $199.00. ISBN 13: 987-1-032-55641-3.